Internet Consumption Patterns and Their Influence on Emotional and Cognitive Well-Being Among Young Individuals in University - Faridoon Ayobi; Ahmad Farhad Rajab Zada; Sayed Ehsan Shamsi (Current Educational Review, 2026)
The proliferation of internet connectivity has fundamentally transformed social, academic, and recreational behaviors among university students worldwide. This study investigates the nature of internet consumption patterns and their multifaceted influence on emotional and cognitive well-being among young university students. A cross-sectional survey was conducted with 646 undergraduate students (mean age = 20.6 years, SD = 1.82) recruited from four major Afghanistan universities. Validated instruments were administered, including the Warwick–Edinburgh Mental Well-Being Scale (WEMWBS), the Generalized Anxiety Disorder Scale (GAD-7), the Patient Health Questionnaire (PHQ-9), and a researcher-developed Internet Usage Pattern Inventory (IUPI). Data were analyzed using descriptive statistics, Pearson correlation, one-way ANOVA, and multiple linear regression. Results demonstrated that 61.1% of participants exceeded six hours of daily internet use, primarily for social media and entertainment. Significant negative correlations were found between daily usage duration and emotional well-being (r = −0.451, p < .001), cognitive concentration (r = −0.389, p < .001), and academic GPA (r = −0.389, p < .001). Conversely, purposeful educational use was positively associated with academic outcomes (β = +.214, p < .001). Nighttime screen exposure emerged as a critical mediator of sleep quality and subsequent mood disturbance. The regression model accounted for 46.7% of variance in well-being scores (R² = 0.467, F(5, 640) = 112.4, p < .001). These findings underscore the urgency of developing digital literacy interventions and university-level policies to cultivate healthier, more intentional internet consumption habits among young adults